Urgensi Inovasi dan Digitalisasi Pendidikan dalam Membangun Kecerdasan Multitalenta - Sitorus, Panca Abdini; Abrianto, Danny (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2025)
Globalization brings great challenges to the world of education, demanding the education system to adapt through innovation and digitalization. In the era of the Industrial Revolution 5.0, mastery of technology and development of multi-talented intelligence are important so that Indonesia can compete globally. The purpose of this study is to find out how innovation and digitalization build multi-talented intelligence. The research method used is also based on literature studies with data collection techniques based on relevant written sources. Such as the use of E-learning which is one of the results of innovation and digitalization can build multi-talented intelligence, and it is hoped that further research can develop many innovations and digitalization that can build multi-talented intelligence.